Empowering economic independence: POKDAKAN modernization and market integration in Tanjung Rhu Village, Pekanbaru City - Ulfia Hasanah; Evi Deliana; Indra Lesmana; Selly Prima Desweni; Samariadi Samariadi; Afriani Nazara; Annisa Dwi Chandra; Dara Aiko Damantha; Dwi Liana Rahmayuni; Ika Sulistya Ningrum; M Prima; Prasiswi Ningsih; R Sadiah Maharani; Vito Oktariandi MK; Yulisa Rika Sari (Community Empowerment, 2024)
The "Mina Sari Jaya" Fish Cultivation Group (POKDAKAN) in Tanjung Rhu Village, Limapuluh District, Pekanbaru City, is undergoing an economic empowerment program aiming for group financial independence within RT 05 RW 06. This initiative combines legal and fisheries expertise to create a comprehensive community economic development strategy. The program offers training in digital marketing, fisheries business management, and legal aspects of running a business. As a result, the group has successfully developed and packaged processed catfish products like snacks and nuggets in standardized, attractive packaging, increasing market appeal. Additionally, these products are now available on online marketplaces like Shopee and Tiktok Shop, generating potential income for POKDAKAN members. Furthermore, the program facilitated the establishment of a formalized business entity for the farmer group, complete with a notarial deed and a deed of establishment.